2016
DOI: 10.1080/15475441.2016.1180983
|View full text |Cite
|
Sign up to set email alerts
|

Subtlety of Ambient-Language Effects in Babbling: A Study of English- and Chinese-Learning Infants at 8, 10, and 12 Months

Abstract: Prior research on ambient-language effects in babbling has often suggested infants produce language-specific phonological features within the first year. These results have been questioned in research failing to find such effects and challenging the positive findings on methodological grounds. We studied English- and Chinese-learning infants at 8, 10, and 12 months and found listeners could not detect ambient-language effects in the vast majority of infant utterances, but only in items deemed to be words or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 62 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…We set about to evaluate the possibility that CBR might vary with age, language/cultural background, and social circumstance. The results give us pause in reflecting on the simple hypotheses that have previously been investigated regarding such phenomena as ambient language effects (Engstrand, Williams, & Lacerda, 2003; Lee et al, 2017) and the growth of CBR across age in various groups of infants (Oller & Eilers, 1982; Oller et al, 1994; Törölä et al, 2012). In fact the three factors (age, language/culture, social circumstance) interacted significantly, greatly complicating possible interpretations, and suggesting that the development of babbling is sensitive to social circumstances and that social circumstances may also adapt to infant development across time.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We set about to evaluate the possibility that CBR might vary with age, language/cultural background, and social circumstance. The results give us pause in reflecting on the simple hypotheses that have previously been investigated regarding such phenomena as ambient language effects (Engstrand, Williams, & Lacerda, 2003; Lee et al, 2017) and the growth of CBR across age in various groups of infants (Oller & Eilers, 1982; Oller et al, 1994; Törölä et al, 2012). In fact the three factors (age, language/culture, social circumstance) interacted significantly, greatly complicating possible interpretations, and suggesting that the development of babbling is sensitive to social circumstances and that social circumstances may also adapt to infant development across time.…”
Section: Discussionmentioning
confidence: 82%
“…It is worth noting that research on the effect of ambient language differences on babbling has focused not on CBR but on the phonotactic, phonetic or acoustic content of babbling (Kern, Davis, & Zink, 2009; Levitt & Wang, 1991; Vihman & de Boysson-Bardies, 1994; Whalen, Levitt, & Goldstein, 2007). We did not monitor the content of CB types (e.g., CV, CVC…) produced by the two groups of infants in the present study, but in another study (Lee, Jhang, Chen, Relyea, & Oller, 2017), we investigated possible ambient-language effects in babbling in English- and Chinese-learning infants at 8, 10, and 12 months. We found that neither English nor Chinese adult listeners could tell if a non-canonical utterance was produced by an English- or a Chinese-learning infant.…”
Section: Discussionmentioning
confidence: 95%
“…As early as 5 months old, infants are able to recognize their own name (Delle Luche et al, 2017) and start associating sounds and words with objects (Gogate and Hollich, 2010). During the second half of the first year, infants start vocalizing and babbling (Lee et al, 2017), followed by using words around their first birthday (Rose et al, 2009). From toddlerhood, children undergo a rapid development in the amount of words they can produce (Dale and Goodman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In our second analysis, wherein cries were treated as nested within infants, we anticipated no differences between the language groups. Here, our rationale was that we find no convincing empirical support for any language‐based differences in sound production prior to the latter half of the first year (see also Kuhl, ; Lee, Jhang, Chen, Relyea, & Oller, ) and little theoretical support for such a phenomenon in models of the mechanics and neurophysiology of neonatal crying (e.g., Golub & Corwin, ; Lester & Zeskind, ; Lieberman, ; Newman, ; Porter, Porges, & Marshall, ).…”
mentioning
confidence: 91%